Anxiety and depressive symptoms in health-care workers managing COVID-19 patients: A cross-sectional study - Joel Sabu; K Priya Nayak; Joshua S Chacko; Aiswarya Roy Karintholil (Wolters Kluwer Medknow Publications, 2022)
Background: Health-care professionals managing the pandemic are at higher risk of developing psychological distress and posttraumatic stress symptoms. The study highlights the importance of evaluating mental health among health-care workers to improve efficiency at work and also proves to be a major step to prevent suicide among health-care workers. Materials and Methods: The authors conducted a cross-sectional questionnaire-based clinical study, using the Depression, Anxiety, and Stress Scale-21 to assess stress, anxiety, and depressive symptoms among doctors and nurses managing COVID-19 patients in Karnataka. Results: Of 233 participants, 3 (1.3%), 27 (11.6%), 15 (6.4%), and 159 (68.2%) participants were suffering from mild, moderate, severe, and extremely severe anxiety respectively; 17 (7.3%), 32 (13.7%), 21 (9%), and 131 (56.2%) are suffering from mild, moderate, severe, extremely severe depressive symptoms, respectively; 15 (6.4%), 19 (8.2%), 26 (11.2%), and 114 (48.9%) are suffering from mild, moderate, severe, and extremely severe stress, respectively. The study also showed that health-care workers who had faced an epidemic in the past were able to cope up with the change in a scenario as compared to those who had not in the past. Conclusion: The study shows the prevalence of stress, anxiety, and depressive symptoms in doctors and nurses. It also shows that people who had exposure to a pandemic in the past were able to cope up better with the situation.